Bioaccumulation of heavy metals by macrophytes in Ghodaghodi Lake, a Ramsar site in Nepal (Nepal Journal of Environmental Science, 2024)
This research investigates the heavy metals (Zn, Cd, Cu, and Pb) concentration in water, sediments, and macrophytes in Ghodaghodi Lake during the winter and summer seasons of 2019 to find out the bioaccumulation of metals and phytoremediation potential of locally available macrophytes. An atomic absorption spectrophotometer with an acid digestion method was used for the analysis of heavy metals. The mean heavy metals concentration during the summer and winter seasons were in the order of Zn > Cu > Pb > Cd in water and sediments. The mean concentrations of Cd, Cu, and Pb were significantly higher in winter (0.79±0.71, 12.99±3.16, and 11.39±6.88 mg/g, respectively) than in summer season (0.01±0.00, 9.13±5.21, and 2.16±6.64 mg/g, respectively) in sediments which is also supported by geo-accumulation index. Zinc had also higher concentrations in winter (65.29±13.13 mg/g) compared to summer (44.00±21.08 mg/g), though not significant.  Ludwigia sp. was more capable of accumulating heavy metals than the Nymphaea sp. in the winter season. On the other hand, Nelumbo sp. was more effective in accumulating heavy metals (except Zn) compared to Ludwigia sp. in the summer season. The highest bioaccumulation factor (macrophyte/sediment) for Ludwigia sp. (common in both seasons) was observed for Cd in winter and Pb in summer season. Thus, although there were some variations in the potentiality of bioaccumulation among the species, these macrophytes are capable of accumulating heavy metals providing scope in the bioremediation field.